If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 = 9y Reorder the terms: 2 + 3x = 9y Solving 2 + 3x = 9y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3x = -2 + 9y Combine like terms: 2 + -2 = 0 0 + 3x = -2 + 9y 3x = -2 + 9y Divide each side by '3'. x = -0.6666666667 + 3y Simplifying x = -0.6666666667 + 3y
| 2d+8=28 | | 5x-5=2(3x-1)-2(x+3)+7 | | 9-4x=15-12x | | 18=4 | | 4+7x=6x-7 | | 5t+7=20 | | 70-5x=3x+18 | | 7x^2+x-3=0 | | 9-8x=55-22x | | 4x^2+61x+180=0 | | -15-11y=-9-3y | | 3(x+4)=2(2x-5)+13 | | 8x-1=11+4x | | 5(2x+7)=25 | | 6-7x=46-14x | | 15x^2-28+5=0 | | h^2+10h=-21 | | 5(x-6)+6=7(x+2)-6 | | 3x+8=-62-7x | | 5x+10=11-4x | | 6.4=x+3.7 | | 2x^2+13x+33=12 | | -16t+t+0=0 | | 4x-16=2x+2 | | -4t^2+t+0=0 | | -[9z-(15z+3)]=3+(5z+4) | | 0.5x-4+2x=5 | | b^2-7b-18=0 | | 2[k-(4k+13)+3]=2(k+10) | | 2x-4+2x=5 | | (x-8)-11=-10 | | 0.8p=32 |